Frekuensi dan Lama Menyusui terhadap Inisiasi Menstruasi - Farida Juliantina Rachmawaty (Berita Kedokteran Masyarakat (BKM), 2003)
Background: The use of contraceptive devices has been well accepted by Indonesian people as a mean for birth spacing. However, users commonly face side effects of the contraceptive devices.Objective: The purpose of this study was to know the association between frequency and the length of breastfeeding period on the initiation of postnatal menstruation. Methods: This study was a retrospective study with an analytical approach. The sub-jects were 96 mothers at Sinduadi village, who had child or children under 5 years old. Mothers who were using hormonal birth control at the time of the study were excluded. Statistical analysis was done by using Spearman correlation and Kruskal Wallis test. Results: In mothers who were less than 35 years old, there was a significant correla-tion between the frequency of lactation and the initiation of menstruation